Structural and Optical Properties of Electrodeposited Porous SnO2 Films: Effect of Applied Potential and Post Deposition Annealing Treatment. Issue 1 (January 2015) - Arote, Sandeep A.; Tabhane, Vilas; Gunjal, Shashikant D.; Mohite, Kakasaheb C.; Pathan, Habib; Bhattacharya, Bhaskar
Summary Nanocrystalline SnO2 film was prepared by cathodic electrodeposition method and its structure and optical properties were studied by X‐ray diffraction, scanning electron microscopy and UV–visible spectroscopy. The effects of applied potential and post deposition annealing on the structural and optical properties of the SnO2 were studied. It was observed from XRD that, the SnO2 film synthesized at 3 V and annealed at 250 °C showed orthorhombic phase with crystallite size of about 10 nm. The morphological study revealed that the samples having porous nature with the network of spherical shape particles. From UV–visible absorption, the band gap of sample was observed of about 3.9 eV. The water contact angle measurements were studied to see the effect of annealing temperature on the hydrophilicity/ Wettability of the film. The SnO2 surface was hydrophilic, but its hydrophilicity decreased considerably after post deposition annealing. Further the samples were used for dye sensitized solar cell applications and the results were discussed.